The fixed exchange rate in Barbados : crisis and adjustment - Crowe, Christopher ([Caribbean Centre for Money & Finance] [St. Augustine]TT, 1999)
Examines the rationale behind Barbados's exchange rate policy and its implications for broader macroeconomic management.